A Case of Meig’s Syndrome Mimicking Ovarian Malignancy: A Diagnostic Challenge - Göç, Göksu; Kahraman, Korhan; Taşkın, Salih; Koçbulut, Evren; Ortaç, Fırat (Gynecology Obstetrics & Reproductive Medicine, 2012)
Ovarian malignancies, especially in advanced stages, are typically presented by ascites and elevated serum Ca-125 levels. Rarely pleural effusion could be seen in these cases due to metastasis or diaphragmatic transportation. Meig’s syndrome defines coexistence of a benign ovarian tumor (fibroma, tecoma or granulose cell tumor), ascites and hydrothorax. In this report, a case of postmenauposal adnexial mass with acute ascites and elevated serum Ca-125 level, that was suspicious for an adnexial malignancy preoperatively. Intraoperative frozen section analysis revealed ovarian tecoma. Meig’s syndrome is a benign pathology that mimicks ovarian malignancy. Differential diagnosis of these two situations is a diagnostic challenge especially in postmenauposal women. Intraoperative frozen section is an important diagnostic method for accurate diagnosis and proper treatment.